Analisis Kenaikan Passenger Service Charge terhadap Peningkatan Pelayanan Penumpang di Terminal Keberangkatan Bandar Udara Internasional ‘Sultan Aji Muhammad Sulaiman’ (SAMS) Balikpapan - Dzunnurain, Muhammad Faruq Syera; Ginusti, Gallis Nawang (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
This study aims to analyze the implementation of the increase in Passenger Service Charge (PSC) rates on improving service quality and passenger satisfaction at the Departure Terminal of SAMS Balikpapan International Airport. This airport has experienced a significant increase in the number of passengers since East Kalimantan was designated as the location of the Indonesian Capital City (IKN), so that an increase in service quality is needed that is balanced with the increase in PSC rates. The study uses a mixed methods approach, namely a combination of quantitative and qualitative methods. The quantitative method is carried out through a Customer Satisfaction Index (CSI) survey to measure the level of passenger satisfaction with service aspects such as cleanliness, comfort, security, and speed of service. The qualitative method is carried out through in-depth interviews with airport managers and comparing it with documentation from the Level of Service (LoS) data of facilities and service processes at the departure terminal. An integrated analysis of quantitative and qualitative data provides a comprehensive picture of the impact of the increase in PSC rates on service quality. The results of the study show that the increase in PSC rates has a positive contribution to improving facilities and services, which has an impact on increasing passenger satisfaction. However, service improvements must continue to be made so that the rates charged can be accepted by service users and support sustainable air transportation growth.